Analytical method for determining the saturation point of superplasticizers in cement pastes using the Marsh cone - Silva,O. F. da (2019)
Abstract The optimum dosage of superplasticizer (SP) additives is determined by the saturation point of SP (SPS), obtained on cement paste by the utilization of the Marsh cone. Obtaining the SPS is important because it defines the amount of SP that should be used in concrete dosages when it is necessary the reduction of water demand and the improvement of the workability. The SPS is determined by methods that use the angles defined by the slope of the flow curve, which are obtained through geometric and visual resources. However, depending on the curve shape, these methods can provide inaccurate results. For this reason, this study analyzed the utilization of the existent geometric methods and proposed a new analytic method of SPS determination. It is noteworthy that the proposed analytical method (PAM) was developed by a numerical implementation to obtain the representative function of paste flow. The SPS is determined from the solution of the phenomenon differential equation and can be used linked to a computational environment in concrete composition calculation. PAM was applied and evaluated in different flow curves obtained by several authors.